Analisis Potensi Pajak Daerah dengan Pendekatan Makro-Mikro di Kota Serang - Muhammad Angga Anggriawan; Kenedi Kenedi; Hadi Kurniawanto (Politeknik Ganesha Medan, 2023)
The development of hotel taxes and restaurant taxes in the city of Serang in the last 5 years has shown a decline. In the last 2 years, namely 2022 and 2021, there has been a negative trend, aka a decrease in the percentage of revenue realization. This is not the same as data for 2020, 2019 and 2018, which shows a positive trend in its realization. The research method used is a quantitative method using secondary data obtained from the offices of BAPENDA, BPKAD and DINKOP UKM. This study uses 2 macro and micro approaches, namely the macro approach using trend analysis linked to the realization of annual taxes, then the micro approach uses secondary data originating from DINKOP UKM on the basis of calculating multiplying the estimated annual turnover of the taxpayer against the effective tax rate. The analytical tool used is trend analysis based on the time series method. The results of the study show that based on the macro approach, the potential for hotel tax and restaurant tax revenues is projected to be very large, this is in line with the results of the micro approach. This shows that the two types of taxes make a sizable contribution to regional tax revenues, provided that the realization can proceed properly so that the amount of local tax revenue collected is in accordance with projections.